Guest Editorial Special Section on Electronic–Photonic Integrated Circuits (EPIC) - Firooz Aflatouni (IEEE Open Journal of the Solid-State Circuits Society)
Electronic-photonic co-design, where the large bandwidth available around the optical carrier, high quality factor optical resonators, low-loss optical interconnects and signal distribution, and highly sensitive photonic sensors are concurrently utilized with sophisticated analog, radio frequency, digital, and mixed signal electronic circuits has improved the performance of many systems for applications ranging from sensing and imaging to communication and computation.